Giant Hidrocystoma of the Orbit Presenting with Inversion and Ptosis of the Upper Eyelid - Melis Palamar; Banu Yaman; Taner Akalın; Ayşe Yağcı (Türk Oftalmoloji Dergisi, 2017)
A case of giant hidrocystoma of the orbit in a 57-year-old female causing pain, epiphora and ptosis is reported. The cystic mass was totally excised as a whole. Histopathologic examination revealed eccrine hidrocystoma of the orbit. Hidrocystoma must be considered in the differential diagnosis of patients presenting with periocular masses causing pain and ptosis.